Entrepreneurial Orientation, Firm Resources And Internationalisation Of Smes - Ngoma, Muhammed (Universiti Sains Malaysia, 2016)

(untitled)
This study investigates entrepreneurial orientation (EO) and firm resources as predictors of SMEs internationalization. The study also examines the mediating and moderating effects of firm resources on the relationship between EO and SME internationalization. The key research question is “to what extent do EO and firm resources predict internationalization of SMEs?” Design/methodology/approach – The study adopts a cross-sectional survey to collect data from a cross industry sample of 248 SMEs, with the use of a multi-dimensional self-administered instrument. A few interviews were also conducted with the SME owners. Findings – The results demonstrate that entrepreneurial orientation and firm’s resources are significantly related to and strongly predict internationalization of SMEs. The study established that besides firm resources being a moderator in SME internationalization, firm resources also provide partial mediation to the relationship between EO and SME internationalization. Implications and limitations – By establishing that EO and firm resources not only individually have significant effects on firm internationalization but also interact to drive SME internationalization, this study contributes to the corpus of literature on internationalization of SMEs in Uganda. The managers of SMEs could enhance the internationalization of their firms by adopting entrepreneurial orientations through innovativeness, proactiveness and risk taking. They should also acquire the requisite physical, human and organizational capital resources. In terms of limitations, the study adopted a cross sectional approach that has deficits of examining the causal-effect relationships. Therefore future studies could consider adopting longitudinal approaches. Originality/value – The paper provides contextual evidence from a developing country that the more the SME owners get inclined to EO (risk taking, proactiveness and creative innovations) and build resources for their firms, the more they can easily join the international business arena